Pengembangan Sistem Informasi Penjadwalan Tatap Muka dan Konsultasi Mahasiswa dengan Dosen Fakultas Ilmu Komputer Universitas Brawijaya - Azhar Ogi; Yusi Tyroni Mursityo; Djoko Pramono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Faculty of Computer Science, Brawijaya University is one of the faculty which has enormous students and lecturers with various activities. Some cases of student's activities must be involved lecturers such as sending message to make an appointment, hence problems arise, students frequently don't get any feedback from lecturer. Based on these problems, information system development is implemented to help and use by lecturer and student. The development process is performed by using Rational Unified Process (RUP) development metho, which its dynamic and iterative, thus can be make it easy to develop information system.. First, the inception phase, bussines process analysis focused on schedule arrangement, make an appointment, and rescheduling. Second, the elaboration phase, the result of user requirements analysis are 14 functional requirements and 1 non-functional requirement to support main functional. Third, the construction phase is carried out, the black-box testing was done through 28 test cases. The conclusion is system can be running successfully. Compatibility testing was done and the result is it can be running on 6 different browsers without issues. The last phase is transition, the user acceptance test (UAT) was done on each actor (both lecturers and students) with the results of 100% acceptance rate for lecturers and 82,86% for students. It can be concluded that all actors are very consent with the scheduling information system functionality that has been developed. Through these development, it generate an information sytem that facilitate lecturers to setup availability, rescheduling, cancellation of appointment, and students will able to make an appointment based on lecturer's availability.